The Effect of The Audit Committee, Auditor Industry Specialization, Earnings Volatility on Audit Report Lag With Company Size as A Moderation Variable - Kireyna Nastiti Tafiandra Putri; Sekar Mayangsari (CV. Publikasi Indonesia, 2024)
This study aims to examine the effect of Audit Committee, Auditor Industry Specialization, Earnings Volatility on Audit Report Lag with Company Size as a Moderating Variable. This study uses secondary data obtained from financial reports and annual reports. The research population is companies in the Properties and Real Estate sector listed on the Indonesia Stock Exchange (BEI) for the period 2018 - 2022. The data collection method in this study was purposive sampling. The sample that met the criteria was 104 company data for 2018 - 2022. The data analysis method used was a quantitative data analysis method using SPSS version 27 to process the data using multiple linear analysis.The results obtained from this study are that the influence of the audit committee has no effect on Audit Report Lag. Auditor Industry Specialization has no effect on Audit Report Lag. Earnings Volatility has a positive effect on Audit Report Lag. Company size is unable to strengthen the effect of audit committee on Audit Report Lag. Company size is unable to strengthen the effect of Auditor Industry Specialization on Audit Report Lag. Company size is able to weaken the effect of Earnings volatility towards Audit Report Lag